2017
DOI: 10.2147/ijn.s124276
|View full text |Cite
|
Sign up to set email alerts
|

The functional curcumin liposomes induce apoptosis in C6 glioblastoma cells and C6 glioblastoma stem cells in vitro and in animals

Abstract: Glioblastoma is a kind of malignant gliomas that is almost impossible to cure due to the poor drug transportation across the blood–brain barrier and the existence of glioma stem cells. We prepared a new kind of targeted liposomes in order to improve the drug delivery system onto the glioma cells and induce the apoptosis of glioma stem cells afterward. In this experiment, curcumin was chosen to kill gliomas, while quinacrine was used to induce apoptosis of the glioma stem cells. Also, p -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 52 publications
(49 reference statements)
1
42
0
Order By: Relevance
“…Furthermore, the synergistic effect of curcumin and stem cells has been reported in an animal model of spinal cord injury (SCI) (Ormond et al., 2014; Ruzicka et al., 2018). Nevertheless, there is controversy regarding the proliferative effects of curcumin on stem cells (Kang, Cha, & Jeon, 2006; Wang et al., 2017). Hence, the present study aimed to address the efficacy of curcumin in combination with autologous transplantation of adult NS/PCs and PM in an animal model of acute brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the synergistic effect of curcumin and stem cells has been reported in an animal model of spinal cord injury (SCI) (Ormond et al., 2014; Ruzicka et al., 2018). Nevertheless, there is controversy regarding the proliferative effects of curcumin on stem cells (Kang, Cha, & Jeon, 2006; Wang et al., 2017). Hence, the present study aimed to address the efficacy of curcumin in combination with autologous transplantation of adult NS/PCs and PM in an animal model of acute brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used to enhance the oral bioavailability of hydrophobic drugs. Several studies have confirmed that encapsulating curcumin in liposomes enhances its hydrophilicity by ninefold compared to unformulated curcumin . Furthermore, curcumin entrapped within liposomes coated with chitosan shows better pharmacokinetic profile.…”
Section: Pharmacokinetics/bioavailability Of Curcumin: Problems and Pmentioning
confidence: 99%
“…Furthermore, curcumin entrapped within liposomes coated with chitosan shows better pharmacokinetic profile. Here, the encapsulation efficacy was reported to be 97.40% . Reports also indicate that co‐administration of lecithins improves the bioavailability of curcumin.…”
Section: Pharmacokinetics/bioavailability Of Curcumin: Problems and Pmentioning
confidence: 99%
See 2 more Smart Citations